Speakers, Call for Abstracts, Program - Schultz-Granberg, Joachim; Blatt, Mellina (EAAE Annual Conference Proceedings, 2025)
Rethinking positions in architectural education, research and practice. Call for papers and concepts for the 2024 EAAE Conference in Münster. Astronaut William Anders’s spontaneous enthusiastic reaction on December 24, 1968 during the Apollo 8 mission led to one of the most influential photo- graphs ever taken.2 Showing the Earth as a beautiful, vulnerable and seemingly self-contained system from far beyond its boundaries inspired environmental movements around the globe. While scientists and environmentalists raised the awareness of our planetary limitations, the Club of Rome report “Limits to Growth” being their most promi- nent statement, architectural practice and academia largely remained confined within the predominant image of architectural production of “less is more”...